The Jesuit College from Kamianets-Podilskyi and Its First Attempt to Organize a Jesuit Mission in Moldavia (1610) According to New Evidence Found in the Archivum Romanum Societatis Iesu - MARINESCU, Diana (Studia Universitatis Babeș-Bolyai Historia, 2025)
Shortly after the foundation of the Jesuit College from Kamianets-Podilskyi in Southern Poland at the beginning of the 17th century, the Polish Jesuits tried to establish a permanent mission in Moldavia, too. Analysing new evidence discovered in the Jesuits archives in Rome, the present paper tries to reconstruct the circumstances of the Jesuits’ arrival in Iași in 1610, their meetings with the Prince Constantine Mohyla (1607-1611), the voivode of Moldavia, with his mother, Lady Elisabeth Mohyla, and with the Court, the missionary expeditions undertaken in the surroundings of the capital, as well as the events that followed the dethronement of the ruler and the installation of Stephen II Tomșa (1611-1615) on the throne by the Turks, including the attempts of the Mohyla family – now refugees in Poland – to seize the power again in Moldavia. Rezumat: Imediat după fondarea Colegiului iezuit din Camenița, iezuiții polonezi de la nou-înființata instituție au încercat să pună bazele unei misiuni stabile și în Moldova. Pe baza unor documente inedite descoperite în arhivele generale ale iezuiților de la Roma (Archivum Romanum Societatis Iesu), articolul de față reconstruiește împrejurările sosirii iezuiților la Iași în 1610, întrevederile acestora cu domnitorul Constantin Movilă (1607-1611), cu doamna Elizabeta Movilă și cu Curtea, expedițiile misionare întreprinse în împrejurimile capitalei, precum și evenimentele care au urmat detronării domnitorului și instalării lui Ștefan Tomșa al II-lea (1611-1615), inclusiv tentativele Movileștilor, refugiați în Polonia, de a prelua din nou puterea în Moldova. Cuvinte-cheie: misiuni iezuite, colegiul iezuit din Camenița, Moldova, familia Movilă